Radial Variation in Fibre Length and Wood Density of Mellanorrhoea usitata Wall - Sharma, C. L.; Sharma, M.; Carter, M. Jimmy (Indian Forester, 2013)
Mellanorrhoea usitata is one of the most important timber species of Manipur. The present study reports information about variations of wood properties from pith to periphery in this species. The study revealed a gradual increase in fiber length from pith to bark. The wood density gradually increased in heartwood from the pith but decreased towards the periphery in the sapwood. The effect of fiber length on wood density is found non-significant.